Proposed Improvement for Service Quality in Obsgyn Outpatient Unit of Klinik Utama Kartini Using Servqual Method and Kano Mode - Ullytha, Gittha; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2014)
Abstract— Indonesia healthcare industry is growing rapidly in recent years, this condition has led to the increase of competition between healthcare providers available on the industry. Nonetheless, with the government plan to implement the National Health Insurance program (JKN) by January 2014, and the increase of demand from community for higher standard of services, the healthcare providers are required to improve their service quality. Klinik Utama Kartini, which was established in 1979, is a health clinic which specializes in obstetrics and gynecology (obsgyn). From January 2011 up to May 2013, there have been decrease in number of patient visit on obsgyn outpatient. This is partly due to the increased competition in health care industry and also since the quality of services provided by the clinic (particularly in the obsgyn outpatient unit) have not meet its customers expectation.To find the root causes which led to reduction in the number of patient visit in the obsgyn outpatient unit, some analyses were conducted. An internal analysis was conducted by analyzing Segmenting, Targeting, Positioning (STP) and the marketing mix (7P) of the clinic, analysis of business situation was conducted using Porter's Five Forces, and analysis of the quality of services was conducted by using Servqual method and Kano Model. Based on the above analyses, it was found that the root causes of the problem are the absence of SOPs and employee regulations, the lack of management in the field of human resources, lack of management relating to promotion activities, and there is need to renovate some tangible factors on the clinic.This study suggests the existence of seven attributes of Servqual Method which should be put as priorities to be improved and also there is need of improvement on promotion activity in the clinic. Keywords: Klinik Utama Kartini, service quality, Servqual Method, Kano Model